ARE CYBERBULLYING INTERVENTIONS AND CRIMINAL LAW PREVENTION EFFECTIVE? (A REVIEW OF CYBERULLYING LEGISLATION IN IRAQ) - Ibrahim Shakir Mahmood (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Cyberbullying is a serious problem which, globally, adversely affects people’s mental health, their sense of security and well-being. Despite the ease of access to the Internet and the widespread opportunities this offers for cyberbullying, in Iraq, little attention has been devoted to researching this problem and, consequently, relevant legislation has been slow to develop. However, in recent years some attempts have been made to regulate internet interactions to afford some level of protection to individuals. For example, the Draft Law of Electronic Signature and Electronic Transactions (78) of 2012, the Project National Informatics Commission Act,Law No. (31) for the year 2013 ratification of the Arab Convention for Combating Cybercrime, Law of ratification of the Electronic Signature Regulation Agreement No. (101) of 2012 and a Project Communications and Informatics Law have attempted to address issues related to the nature and content of online interactions. Nevertheless, these measures have been limited in their implementation due to the impacts of cyberbullying being poorly understood in Iraq. Consequently, there is little appreciation of the vulnerability of certain groups, especially school and university students, to the often devastating effects of cyberbullying. The current study contributes to the increasing body of research into the phenomenon of cyberbullying and, particularly, is a response to the requests by scholars for more descriptive accounts of instances of online intimidation and its effects.ntent and nature of online bullying incidents. The adequacy of current Iraqi legislation touching on cyberbullying is examined and the impediments to reforming current legislation or to formulating new legislation are highlighted. The principal challenges to law reform, which are investigated in this article, include the lack of clarity in defining cyberbullying, the problem of establishing what constitutes evidence of intention to cause harm to others through online interactions, lack of surveillance, the role of technology and the issue of defining the age of criminal responsibility.